One-Year Insights into the GLOBOSTAD Multinational Prospective Observational Study of Patients Receiving Dupilumab for Atopic Dermatitis - Calzavara-Pinton, Piergiacomo; Chu, Chia-Yu; Lapeere, Hilde; Rossi, Mariateresa; Ferrucci, Silvia M; Chung, Wen-Hung; Fougerousse, Anne-Claire; Fomina, Daria S; Holzer, Gregor; Čelakovská, Jarmila; Al-Ahmad, Mona; Tzellos, Thrasyvoulos; et al. (Advances in therapy, 2025)
INTRODUCTION: Currently, limited data are available on long-term use of dupilumab to treat atopic dermatitis (AD) in a multinational real-world setting. The aim of this analysis was to report the interim 1-year data for patients with AD enrolled in the GLOBOSTAD registry, including treatment patterns, dupilumab effectiveness and safety, and healthcare burden. METHODS: GLOBOSTAD is an ongoing, 5-year, multinational, prospective, observational study of adult/adolescent (aged ≥ 12 years at baseline) patients with AD who initiated dupilumab in real-world settings according to their local country-specific prescribing guidelines. Outcomes were evaluated at baseline and at 3, 6 and 12 months and included Eczema Area and Severity Index (EASI) total score, SCORing Atopic Dermatitis (SCORAD) total score, percent body surface area (BSA) affected, Patient-Oriented Eczema Measure (POEM), Dermatology Life Quality Index (DLQI) total score for adults or Children's Dermatology Life Quality Index (CDLQI) total score for adolescents and pruritus Numeric Rating Scale (NRS) total score. RESULTS: At the interim 1-year cut-off (March 2023), 955 patients were enrolled in GLOBOSTAD, and follow-up data were obtained from 903 patients. After dupilumab initiation, mean improvements in effectiveness outcome measures from baseline to month 3 were EASI from 25.1 to 6.1, SCORAD 59.3 to 25.3, POEM 19.7 to 8.7, DLQI 13.7 to 5.3, CDLQI 12.2 to 2.7 and pruritus NRS 6.3 to 2.5, with each measure exceeding the minimal clinically important difference. These positive changes in effectiveness outcomes were maintained or further improved through 12 months since treatment initiation. AD-related hospitalizations and emergency room or urgent care facility visits decreased from 11.1% to 1.7% from baseline to month 12. CONCLUSIONS: In a multinational real-world setting, dupilumab demonstrated rapid, robust and sustained effectiveness in patients with moderate-to-severe AD across multiple disease domains, including AD signs, symptoms, quality of life and emergency/urgent care visits. Safety was consistent with the known dupilumab safety profile. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov Identifier NCT03992417.
Keywords: Dermatitis, Atopic; Humans; lidé středního věku; Atopic dermatitis; dítě; Quality of Life; Real-world; Child; Female; mladý dospělý; dospělí; výsledek terapie; lidé; humanizované monoklonální protilátky; Long-term treatment; kvalita života; Dupilumab; Adult; Antibodies, Monoclonal, Humanized; ženské pohlaví; stupeň závažnosti nemoci; Male; Middle Aged; Adolescent; Treatment Outcome; Severity of Illness Index; atopická dermatitida; Young Adult; mužské pohlaví; prospektivní studie; mladiství; Prospective Studies